Peran literasi keuangan syariah dan pendapatan terhadap utang konsumsi di Surabaya - Humainy, Mahbub; Nasution, Zubaidah (Universitas Hayam Wuruk Perbanas, 2024)
This research aims to analyze the influence of sharia financial literacy and family income on household consumption debt in Surabaya. This research method uses a quantitative approach through questionnaires to 115 house-holds in Surabaya. The sample in this study was Surabaya City house-holds, which the researchers obtained based on established criteria. The sample that met the criteria was 115 households. Data analysis uses multiple linear regression tests, which are processed through the SPSS application. The research results show that partial sharia financial literacy does not have a significant influence on household consumption debt, while family income has a significant negative influence on consumption debt. The better the sharia financial literacy, the higher the household consumption debt; on the other hand, the higher the income, the lower the consumption debt. The implications of the results of this research are that households play an active role in Sharia financial inclusion but do not understand or study Sharia financial literacy. The high level of household consumption debt is influenced by needs and lifestyle. The household income factor is wiser in its use, where households with higher incomes tend to have lower consumption debt.